Therapeutic appropriation: a new concept in the ethics of clinical research - McDougall, R; Martin, D; Gillam, L; Hallowell, N; Brookes, A; Guillemin, M (BMJ Publishing Group, 2016)
Ethical concerns about therapeutic misconception have been raised since the early 1980s. This concept was originally described as research participants’ assumptions that decisions relating to research interventions are made on the basis of their individual therapeutic needs. The term has since been used to refer to a range of “misunderstandings” that research participants may have. In this paper, we describe a new concept - therapeutic appropriation. Therapeutic appropriation occurs when patients, or clinicians, actively reframe research participation as an opportunity to enhance patients’ clinical care, while simultaneously acknowledging the generalised research aims. To illustrate the concept of therapeutic appropriation, we draw on data from an interview study which we conducted to investigate the experiences of patients and general practitioners involved in clinical trials in primary care. We argue that therapeutic appropriation has two key elements: comprehension that the research project is not necessarily aiming to benefit participants, together with the deliberate use of incidental features of the research for personal therapeutic benefit of various kinds. We conclude that therapeutic appropriation is a useful concept that refines understanding of potential ethical problems in clinical research, and points to strategies to address them.